Poeng Mang Folk Dance Performance by Pratuang Suriyawong - Chaemfa, Kanokphat (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2023)
This academic article aims to study the history, performance approaches, and elements of the show, including analyzing the Poeng Mang folk dance performance of Professor Pratuang Suriyawong as a guideline for practicing and continuing this performance. The results of the study revealed that the Poeng Mang folk dance performance is a new traditional dance created by Professor Pratuang Suriyawong for the first time in the 25th Buddhist century celebrations at Lat Yao District, Nakhon Sawan Province. The dancing posture was inspired by the worshiping spirit ceremony of Peguan (Mon), and the Thai musical instruments used Perng Mang Khok as an accompaniment to the performance, with small cup-shaped cymbals, and cymbals, Grub, and Kong to accompany the rhythm, making the Poeng Mang’s dance performance full of fun and excitement. When the posture dancing is completed, the players will beat the drums as a signal to change to the next move. There are 9 dance postures based on the Mon’s dancing worshiping spirit. Those dance moves come from nature and human way of life, such as in the Mon Thok Pha, Mon Sei Phom, etc. The costume is also imitated from Mon-Burmese, which can be applied to the aesthetics of the performance. According to the results of research and analysis, this paper will provide useful guidance and reference for those who are interested to study and further develop the process of performing this folk dance to prevent it from extinction.